2020
DOI: 10.1080/23802359.2019.1704647
|View full text |Cite
|
Sign up to set email alerts
|

The complete chloroplast genome of Acer pentaphyllum (Sapindaceae), a critically endangered maple endemic to China

Abstract: Acer pentaphyllum is a critically endangered maple confined to the valley of Yalong River in Southwest China. The whole chloroplast genome of A. pentaphyllum was 156,862 bp in length with a typical quadripartite structure, containing a large single-copy (LSC) region of 85,292 bp, a small single-copy (SSC) region of 18,146 bp, and a pair of inverted repeat (IR) regions of 26,712 bp separated among them. Totally 137 unique genes were predicted, comprising 89 protein-coding genes, 39 tRNA genes, and 8 rRNA genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…There are some cp genomes in Sapindaceae s.l. species have been reported and deposited in Gen-Bank database, like Acer [34], Dodonaea [35], Aesculus [36][37][38][39], Dimocarpus [40], most of which were the genus Acer [41][42][43][44][45][46]. We also noticed that previous studies have revealed the complete cp genomes of H. bodinieri and E. cavaleriei [47][48][49], but focus mainly on the size and gene contents of the cp genome, lacking detailed comparative genomic and comprehensive phylogenetic analysis.…”
Section: Introductionmentioning
confidence: 99%
“…There are some cp genomes in Sapindaceae s.l. species have been reported and deposited in Gen-Bank database, like Acer [34], Dodonaea [35], Aesculus [36][37][38][39], Dimocarpus [40], most of which were the genus Acer [41][42][43][44][45][46]. We also noticed that previous studies have revealed the complete cp genomes of H. bodinieri and E. cavaleriei [47][48][49], but focus mainly on the size and gene contents of the cp genome, lacking detailed comparative genomic and comprehensive phylogenetic analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Although some cp genomes in Sapindaceae s.l. species have been reported and deposited in GenBank database, like Acer [34], Dodonaea [35], Aesculus [36][37][38][39], Dimocarpus [40], most of which were the genus Acer [41][42][43][44][45][46]. We also noticed that previous studies have revealed the complete cp genomes of H. bodinieri and E. cavaleriei [47][48][49], but focus mainly on the size and gene contents of the cp genome.…”
Section: Introductionmentioning
confidence: 99%